THE ANTI-ECHINOCOCCIASIS CAMPAIGN IN CYPRUS - ΠΟΛΥΔΩΡΟΥ Κ. (Journal of the Hellenic Veterinary Medical Society, 1974)
The author is referring to the anti - echinococciasis en npaign in Cyprus which started in February 1971. A 15 years program was arranged in order to obtain a complete eradication of the disease. Since the application of this program that is 2 1/2 years 33.748 stray dogs were killed and 2.532 female dogs became sterile by hysterectomy. Information about the disease and its dangers was given by specialized persons or groups to different State staff, slaughterhouses staff, animal breeders, schools» housewives etc. Complementary measures were taken : registration and taxation of dogs» disinfestation etc. The results of this campaign are already very satisfactory. The infestation rate in young ruminants and swine was reduced 83,3 - 95% and in dogs 58.8%. Especially the infestation rate in dogs beign 6.8% during 1972 dropped to 2.8% in the first six months of 1973. The echinococciasis which was a scourge for the animal breeding and the Public Health of Cyprus is on the way of its definite eradication.